PENYELESAIAN AYAT-AYAT ‘DAMAI’ DAN AYAT ‘PEDANG’ DALAM AL-QUR`AN MENURUT SYAIKH YUSUF AL-QARDHAWI DAN SYAIKH ABDUL AZIZ BIN ABDULLAHBIN BAZ - Ali Trigiyatno (Jurnal Penelitian, 2012)
This research was aimed to resolve the appearance of contradictory between peace and war verses in Quran based on Yusuf Qardhawi and Abdullah bin Abdul Aziz binBaz view. The research found that there are similarities between their view in interpreting and understanding those verses, as on prescribing defense jihad, jihad priority, the need for preparation on facing the enemy and the purpose of jihad and other defense.However, it also found a number of differences between the two, as in the matter of jihad thalabi, whether peace verses are replaced by war verses, jihad thalabi purpose, scope and meaning of jihad.